Peran dan Tanggung Jawab Etis Profesional TI dalam Mencegah Kebocoran Data Privasi - Areta Siti Shada Andari; Evy Nurmiati (INDO PUBLISHING, 2026)
Personal data breaches pose a serious threat amid Indonesia's rapid digital transformation, involving government institutions and e-commerce platforms. This article examines the role and ethical responsibilities of IT professionals in preventing privacy data breaches, and proposes an integrated conceptual framework as a practical reference for practitioners. A systematic literature review was conducted on seventeen Indonesian-language scientific sources published between 2021–2026, analyzed thematically across three domains: regulation, professional ethics, and case studies. The review produces the Ethical-Technical Responsibility Framework (ETRF) identifying four dimensions of IT professional obligations technical-preventive, legal compliance, transparency-reporting, and continuous competence development operating across three levels: individual, organizational, and regulatory. Analysis of BPJS Kesehatan and tax data breach cases reveals that ethical failures, not merely technical ones, are the root cause of most incidents. Strengthening IT professional ethics, supported by effective regulation and the establishment of an independent personal data supervisory authority, is a prerequisite for digital privacy protection in